INOVASI PEMBELAJARAN PAI DALAM PENGGUNAAN MEDIA SUMBER BELAJAR DI SMP HAROKATUL YAMANIE TANGERANG - Salahuddin, Salahuddin; Nurasiah, Siti (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2024)
This study aims to improve students' creativity and learning outcomes in Islamic Religious Education (PAI) subjects by utilizing infocus media as a learning resource. The main objective of this study is to overcome traditional learning methods that are less effective in developing student creativity and involvement. By integrating infocus media, it is expected that students can better understand the material on reprehensible morals and be actively involved in the learning process. The methodology used is Classroom Action Research (CAR), which is carried out in two cycles. Each cycle consists of several stages: planning, implementing actions, observation, and reflection. Data collection methods include observation, student learning outcome tests, and interviews with teachers and students. The researcher also used formative tests to assess students' abilities before and after the action. The results of the study showed a significant increase in student learning outcomes and creativity. In the first cycle, the average student learning outcomes increased from 59.00% in the post-test to 65.00%. The increase continued in the second cycle with an average value reaching 78.00%. In addition, student involvement in the learning process also increased, especially in understanding and applying concepts taught through infocus media. In conclusion, the use of infocus media has proven effective in improving creativity and student learning outcomes in Islamic Religious Education subjects, especially in the topic of reprehensible morals